International Technology Transfer Policies - Andrenelli, Andrea (OECD Trade Policy Papers, 2019)
Concerns are growing about policies and measures that restrict market access with the effect of "forcing" technology transfer. Efforts to target forced technology transfer are complicated by the sometimes blurred line between voluntary and mutually agreed upon technology transfers and that which is perceived to be, or is in fact, compelled. This study presents a discussion of the continuum of measures related to international technology transfer (ITT) and aims to identify those measures that pose the greatest concern over their potential to compel disclosure of commercially valuable and sensitive technology. It then briefly presents information on provisions in international trade and investment agreements that are relevant to ITT. The last section presents the perspective from the private sector in order to better understand how firms engage in technology transfers through research collaboration, licensing, joint ventures, and equity investments. The analysis in this report indicates that involuntary technology transfer is a complex issue, and it aims to provide a way for policy makers to think through the issues, to apply a systematic and analytical approach to assessing which policies are of the greatest concern